The Effect of the two Directions of set point in volleyball on its accuracy and reception - Ibrahim, Kahlil (Journal of Physical Education, 2007)
This peper aimed at exploring the effect of the variation of set point direction in volleyball on its accuracy and receiption . It was carred out at a group of volleyball players in Ramadi during the season 2005-2006 . They were (10) in number representing 66.6% of the research population . Spead tests to measure the accuracy of the two skills of set form the two side of the square were carred out through directing the ball to the two opposite corners of the square then receiving in form the ofher two corners in the proporation zone (position 3) . After collecting the data , they were statistically processed using (T2) test for unrelated sharpes and Moro_variation physis and less significant variation test (L.S.D) . The wast important results can be summarized as follows ; Directed sets from right to left are more accurate . Also , sets that take linear direction are more accurate them diagonal direction sets and rice versa concerning set receiption . The researcher recomanded the recessity to variate set zones on the square final line . The some thing is true in regard to set recciring to overcome weakness and develop and improve storage points to arrive at the best results